VD_FINDINFO HC / 2009 / 256 vom 27. Juli 2009 - VD Tribunal cantonal (2009)
PRESCRIPTION, DOLVICE DU CONSENTEMENT, ERREUR DE BASE | 31 CO, 60 CO, 451 ch. 2 CPC, 452 al. 1 CPC, 452 al. 2 CPC, 465 al. 1 CPC, 471 al. 3 CPC